Flashback Canada - Cruxton, J. Bradley; Wilson, W. Douglas; Francis, Daniel; Harrison, Brian; Johnson, Peggy (Oxford Univ. Press, 2008)
About the history of Canada from its creation as a country in 1867 to the outbreak of the First World War in 1914.